Produced waters workshop - Colorado Water Resources Research Institute, author (Colorado State University. Libraries, 2006)
The produced waters workshop was held on April 4-5, 2006 in Fort Collins, Colorado.
Keywords: Oil field brines -- West (U.S.) -- Congresses; Water reuse -- West (U.S.) -- Congresses